2023
DOI: 10.1021/acsapm.2c02102
|View full text |Cite
|
Sign up to set email alerts
|

Perylene Diimide-Containing Dynamic Hyper-crosslinked Ionic Porous Organic Polymers: Modulation of Assembly and Gas Storage

Abstract: A strategy to synthesize hyper-crosslinked polymers with strong visible-light absorption and abundant ionic sites is discussed. This is achieved in a one-pot reaction via the simultaneous Friedel–Crafts alkylation and quaternization reaction between α,α′-dibromo-p-xylene (DBX) and perylene diimide (PDI) substituted with N,N-dimethyl ethylene to result in hyper-crosslinked ionic polymers (HIPs). These HIPs display good surface areas with strong visible-light absorption (400–650 nm) and dispersibility in polar s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 64 publications
0
1
0
Order By: Relevance
“…In sharp contrast, we also found that hierarchical self‐assembly can also occur by increasing solvated solute concentration and without much release of solvent molecules from the solute (Pathwa‐2). Our findings further suggest that the water‐AOS mixture is an exciting solvent medium for uncovering new solvation‐desolvation phenomena in polymeric and supramolecular polymeric systems and synthesizing functional soft materials [63] …”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In sharp contrast, we also found that hierarchical self‐assembly can also occur by increasing solvated solute concentration and without much release of solvent molecules from the solute (Pathwa‐2). Our findings further suggest that the water‐AOS mixture is an exciting solvent medium for uncovering new solvation‐desolvation phenomena in polymeric and supramolecular polymeric systems and synthesizing functional soft materials [63] …”
Section: Discussionmentioning
confidence: 56%
“…Our findings further suggest that the water-AOS mixture is an exciting solvent medium for uncovering new solvation-desolvation phenomena in polymeric and supramolecular polymeric systems and synthesizing functional soft materials. [63]…”
Section: Discussionmentioning
confidence: 99%
“…Synthesis of cPDI: cPDI has been synthesized according to the literature methods. [62,63] Preparation of cPDI involves a two-step reaction, in the first phase PDI was prepared by adding 3,4,9,10 perylene tetracarboxylic dianhydride (1 g, 2.55 mmol) and N,N-dimethylethylenediamine (0.89 g, 10.19 mmol) to the imidazole (10 g) and the reaction was carried out for 8 h at 120 °C. The obtained precipitate was filtered and washed repeatedly with methanol to remove the imidazole.…”
Section: Methodsmentioning
confidence: 99%
“…The conjugated microporous polymer (CMP) is a new type of porous material made only from covalent bonds and exhibits a rigid backbone, large surface area, and high stability. [5] Various organic building blocks have been used to synthesize the CMP, and the CMP plays an important role in applications such as gas storage, [6] catalysis, [7] and sensing, [8] etc. The incorporation of porphyrin into CMP reduces porphyrin aggregation, which in turn enhances its photocatalytic degradation performance.…”
Section: Introductionmentioning
confidence: 99%